Lessons Learned From the Battlefield and Applicability to Veterinary Medicine – Part 2: Transfusion Advances - Edwards, Thomas H.; Pusateri, Anthony E.; Mays, Erin Long; Bynum, James A.; Cap, Andrew P. (Frontiers in Veterinary Science, 2021)
Since the inception of recent conflicts in Afghanistan and Iraq, transfusion practices in human military medicine have advanced considerably. Today, US military physicians have recognized the need to replace the functionality of lost whole blood in traumatic hemorrhagic shock and whole blood has become the resuscitation product of choice on the battlefield. Building on these wartime experiences, military medicine is now one of the country’s strongest advocates for the principle of hemostatic resuscitation via balanced blood components. The development of canine freeze dried plasma offers a potentially new and useful therapeutic which has great potential to be used for hemostatic resuscitation close to the point of injury as a bridge to full resuscitation. Finally, the potential use of chilled platelets, which has been championed by the military transfusion community, could increase the availability of canine blood products, which have traditionally been difficult to resource. Advances in battlefield medicine have numerous parallels in veterinary medicine, any of which are potentially available today in both general and referral small animal practices. The lessons learned from human traumatic injuries are ripe for translation into veterinary medicine.